PENGEMBANGAN E-LEARNING MELALUI MODUL INTERAKTIF BERBASIS LEARNING CONTENT DEVELOPMENT SYSTEM - Heni Rodiawati; Komarudin Komarudin (Universitas Islam Negeri (UIN) Mataram, 2018)
This study aims to produce teaching materials in the form of e-learning mathematics through interactive module based learning content development system on the material of building a flat side space. This research method is research and development (R&D) based on Sugiyono model that limits to 7 steps that are potential and problem, gather information, product design, product validation, product revision, product trial, and product revision. The feasibility of an interactive module based on a material expert is included in the “Very Decent” category with a percentage score of 82,83%. The media expert’s assessment of this interactive module belongs to the “Very Decent” category with a percentage score of 82,625%. The assessment of linguists to the media is included in the “Very Decent” category with a percentage score of 96%. In a small-scale trial at SMPN 6 Kotabumi it obtained a percentage score of 85,625%, in SMPN 11 Kotabumi scored 87,71%, and in SMP Hang Tuah Kotabumi scored 84,375%, these results place an interactive module on the “Very Interesting” criteria. In large-scale trials in the three schools scored 84,5%, 89,61%, dan 88,61% with the criteria of “Very Interesting.”